Common cis-acting region responsible for transcriptional regulation of Bradyrhizobium japonicum hydrogenase by nickel, oxygen, and hydrogen. - Kim, H (1991)
Bradyrhizobium japonicum expresses hydrogenase in microaerophilic free-living conditions in the presence of nickel. Plasmid-borne hup-lacZ transcriptional fusion constructs were used to study the regulation of the hydrogenase gene. The hydrogenase gene was transcriptionally induced under microaerobic conditions (0.1 to 3.0% partial pressure O2). The hydrogenase gene was not transcribed or was poorly transcribed in strictly anaerobic conditions or conditions above 3.0% O2. Hydrogen gas at levels as low as 0.1% partial pressure induced hydrogenase transcription, and a high level of transcription was maintained up to at least 10% H2 concentration. No transcription was observed in the absence of H2. Hydrogenase was regulated by H2, O2, and Ni when the 5'-upstream sequence was pared down to include base number -168. However, when the upstream sequence was pared down to base number -118, the regulatory response to O2, H2, and Ni levels was negated. Thus, a common cis-acting regulatory region localized within 50 bp is critical for the regulation of hydrogenase by hydrogen, oxygen, and nickel. As a control, the B. japonicum hemA gene which codes for delta-aminolevulinic acid synthase was also fused to the promoterless lacZ gene, and its regulation was tested in the presence of various concentrations of O2 and H2. hemA-lacZ transcription was not dependent on levels of Ni, O2, or H2. Two different hup-lacZ fusions were tested in a Hup- background, strain JH47; these hup-lacZ constructs in JH47 demonstrated dependency on nickel, O2, and H2, indicating that the hydrogenase protein itself is not a sensor for regulation by O2, H2, or nickel.